For example: from the second equation: and then substitute this into the first one: substitute this into : .
I've been going through a textbook and I've came across Simultaneous equations by this point. I can do many, such as:
c = 7d - 2 [1]
3c - 4d = 11 [2]
To do this I subbed c in [2] and did this method:
3(7d-2) - 4d = 11
21d - 4d - 6 = 11
17d = 17
d = 1
And then went back to 3c - 4d = 11
I found that 3c = 15
and c = 5.
However the last question is:
6x - 5y = 27
3y = 1 - 5x
Now I'm pretty sure you don't use the same method as last time so what can I do here